Analisis Faktor Penyebab Ketidaklengkapan Informed Consent Bedah Rawat Inap Rumah Sakit Paru Jember - Rossalina Adi Wijayanti; Rizky Putri Amalia (Jurnal Kesehatan, 2023)
One of the indicators for medical record is 100% for Informed Consent completeness. Based on a preliminary study at Paru Hospital Jember, it was found that average number is at 40,20% of the 102 informed consent files are incomplete. The purpose of this research is analyzing factors brought incompletess filling in surgical  informed consent. This research used a qualitative research method carried out at Paru Hospital Jember February to July 2021. The results showed that the high incompleteness of the informed consent was caused about there is no punishment was received by the officer if he did not fill in the informed consent. Doctors and nurses have never received training about medical records. The SOP does not include the number of completeness filling. The knowledge of doctors in completeness standarts of informed consent are less. The conclusion of this research is the incomplete number of informed consent filling caused the Minimum Service Standars of medical record in hospital cannot be fulfilled. It is because the performance has not been maximized